(untitled) (Global Journal of Human-Social Science, 2021)
Language" is the main tool of communication between people, and it’s an important mechanism to express people’s way of thinking and cultural connotation. "Pragmatics" mainly considers in what context, when, and what to say something and to whom to say it. The language expressions used by people from different cultural backgrounds are quite different. Insufficient understanding of pragmatics will cause language misunderstanding and pragmatic failures. Based on theories on language pragmatics, this article mainly discusses the differences of Chinese pragmatics and pragmatic failures in cross-cultural communication, the influence of different cultures on Chinese pragmatics, the main factors that cause Chinese pragmatic failures in cross-cultural communication, and the ways to avoid such pragmatic failures and misunderstandings.